Unstructured design solutions for information systems using cognitive model - Кошкин, Константин Викторович; Возный, Александр Михайлович; Яни, Анна Юрьевна (Eastern-European Journal of Enterprise Technologies, 2012)
The cognitive modelling method of situations against unstructured decisions in IT projects is described. A mathematical model of information system effective configuration choice is developed